The Effect of Think-Talk-Write (TTW) Strategy on Writing Descriptive Text Ability at SMA Negeri 1 X Koto Diatas - Habibatul Amri; Hamzah Hamzah (Journal of English Language Teaching, 2023)
The study aimed to find out whether or not Think-Talk-Write (TTW) strategy has a better effect on writing ability in descriptive text at SMA Negeri 1 X Koto Diatas compared than discovery learning method. This experimental study was conducted by using a post-test only design in which there is no pre-test given. The population of this research was the grade tenth students of SMA Negeri 1 X Koto Diatas. This study takes two classes of the tenth grade students as the sample. They were X.E3 as the experimental class and X.E1 as the control class. The experimental class was taught by using the Think-Talk-Write (TTW) strategy and the control class was taught by using the discovery learning method. The writing test was used as the instrument. The formula of the study was analyzed by using the independent t-test. It was used to determine whether there was a significance difference between the experimental class and the control class. The result of the data analysis showed that the mean score of the experimental class (81.84) was higher than the mean score of the control class (73.35). Furthermore, the result of the independent t-test in this research stated that the value of sig (2-tailed) is 0.004 which is lower than the significance alpha 0.05. It means that the alternative hypothesis is accepted which stated the TTW strategy give a more significant effect on students’ writing ability in descriptive text than discovery learning. In conclusion, the students who were taught by using Think-Talk-Write (TTW) strategy had better writing scores than the students who were taught by using discovery learning method.